The hidden form of capital spiritual influences in societal progress - Berger, Peter L., 1929-; Redding, S. G. (London ; New York : Anthem Press, 2010)
"The Hidden Form of Capital presents evidence from several parts of the changing world about how the realm of the spirit affects the economy. The idea that societies have economic cultures as well as aesthetic, literary, and artistic cultures is well-embedded in a number of major studies attempting to identify the origins of national wealth and progress. This book provides an original contribution to the debate, by discussing the relationship between religion and the economy not via further theoretical speculation, but through the presentation of analytical evidence from real-life case studies in Europe, Asia, Africa, Russia, and the United States. There is currently a major re-assessment of assumptions about the foundations of societal progress, as the market rationality model is exposed for its moral weaknesses. The emergence of socio-economics as a scholarly field, as well as the embracing of complexity theory and the societal effect in economic analysis, brings the question of cultural effects to the forefront. This collection of studies offers more practical and tangible evidence, especially unique and useful for its comparative aspect. The book skilfully combines this comparative and descriptive character with an accessible writing style intended for a wide audience."--Publisher's description.
Introduction: spiritual, social, human, and financial capital / Peter L. Berger and Gordon Redding -- Do some religions do better than others? / Lawrence E. Harrison -- Spiritual capital and economic development: an overview / Peter J. Boettke -- The possibilities and limitations of spiritual capital in Chinese societies / Robert P. Weller -- How Evangelicanism -- including Pentecostalism -- helps the poor: the role of spiritual capital / Rebecca Samuel Shah and Timothy Samuel Shah -- Flying under South Africa's radar: the growth and impact of Pentecostals in a developing country / Ann Bernstein and Stephen Rule -- Importing spiritual capital: East-West encounters and capitalist cultures in Eastern Europe after 1989 / Janos Matyas Kovacs -- Orthodox spiritual capital and Russian reform / Christopher Marsh -- Islam and spiritual capital: an Indonesian case study / Robert W. Hefner -- Separating religious content from religious practice: loose and tight institutions and their relevance in economic evolution / Gordon Redding.
Includes bibliographical references.
Print version record.
Master record variable field(s) change: 072
Keywords: Economics -- Religious aspects; Aufsatzsammlung; RELIGION -- Christianity -- General; RELIGION -- Christian Life -- Social Issues; Economics -- Religious aspects; Humankapital; Religion; Wirtschaftsentwicklung; POLITICAL SCIENCE / History & Theory; Aufsatzsammlung; Electronic books